Walter B. Wriston and family at Brown University (Tufts Archival Research Center, 2008)
8.6 x 6.2. Left to Right: Ruth Bigelow Wriston (Walter B. Wriston's mother), Henry Merritt Wriston (Walter B. Wriston's father), Barbara Wriston (Walter B. Wriston's sister), Walter B. Wriston, and Barbara Brengle Wriston (Walter B. Wriston's wife) during Henry Merritt Wriston's presidency at Brown University. The print and digital image were created from 'File2821' from the CD titled 'Walter B. Wriston Photographs - CD 2'.